Promoter‐Driven Overexpression in Chromobacterium vaccinii Facilitates Access to FR900359 and Yields Novel Low Abundance Analogs. Issue 8 (28th December 2021) - Pistorius, Dominik; Buntin, Kathrin; Weber, Eric; Richard, Etienne; Bouquet, Caroline; Wollbrett, Séverine; Regenass, Hugo; Peón, Victor; Böhm, Marcel; Kessler, Régis; Gempeler, Thomas; Haberkorn, Anne; et al.
Abstract: Access to the cyclic depsipeptide FR900359 (FR), a selective Gq/11 protein inhibitor of high pharmacological interest and a potential lead molecule for targeted therapy of cancers with oncogenic GNAQ or GNA11 mutations (encoding Gq and G11 respectively), has been challenging ever since its initial discovery more than three decades ago. The recent discovery of Chromobacterium vaccinii as a cultivable FR producer enables the development of approaches leading to a high‐yielding, scalable and sustainable biotechnological process for production of FR, thereby removing this bottleneck. Here we characterize different promoters in exchange of the native promoter of the FR assembly line, resulting in an overexpression mutant with significantly increased production of FR. Thereby, the isolation and structure elucidation of novel FR analogs of low abundance is enabled. Further, we explore the antiproliferative activities of fifteen chromodepsins against uveal melanoma cell lines harboring Gq/11 mutations and characterize the major metabolite of FR formed in plasma. Abstract : The promoter‐driven overexpression of the frs biosynthetic gene cluster, encoding the nonribosomal peptide assembly line for FR900359, in Chromobacterium vaccinii resulted in up to 8‐fold increase in production compared to the wild type. Thereby, the challenging access to FR could be significantly enhanced and novel low abundance analogs of FR were made accessible for characterization of their structures and concerning their growth inhibition of uveal melanoma cell lines.